2020
DOI: 10.1080/23311932.2020.1773094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofenset(Ensete ventricosum) clones for resistance reaction against pathogenicXanthomonas campestris pv. musacearumisolates from Southwestern Ethiopia

Abstract: Enset (Ensete ventricosum) bacterial wilt (EBW) incited by Xanthomonas campestris pv. musacearum (Xcm) is threatening enset production in southwestern Ethiopia. The objectives of this study were to determine the pathogenicity of Xcm isolates and select enset clones resistant to pathogenic Xcm isolates in the study areas. A total of 30 Xcm isolates were subjected to pathogenicity tests on a susceptible enset clone Yeko and all were found pathogenic. Out of 30 pathogenic isolates, three isolates representing thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Over all the, the enset clones vary in reaction bacterial wilt disease (Hunduma et al, 2015). Haile et al, (2020) conducted trial to determine the pathogenicity of Xcm isolates to select resistance/tolerant enset clones. About 30 Xcm isolates were subjected to pathogenicity test on susceptible enset clones called Yeko.…”
Section: Selections Of Disease Resistance Enset Clones Through Conventional Breeding Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over all the, the enset clones vary in reaction bacterial wilt disease (Hunduma et al, 2015). Haile et al, (2020) conducted trial to determine the pathogenicity of Xcm isolates to select resistance/tolerant enset clones. About 30 Xcm isolates were subjected to pathogenicity test on susceptible enset clones called Yeko.…”
Section: Selections Of Disease Resistance Enset Clones Through Conventional Breeding Methodsmentioning
confidence: 99%
“…The disease progressive curve of Nobo enset clone resulted in none progression and lied on X-axis for each isolate combinations. The disease progressive Curve of enset clones Gudiro x Xcm isolates progressed slowly and decreased rapidly and declined to the X-axis in response to recovery of infestation late in the epidemic period (Haile et al, 2020). Haile et al, (2020) reported that, even though all of the Xcm isolate are pathogenic to most of the agro-ecologically adapted enset clones in South-west Ethiopia, some accessions like Gudiro, Maziya, and Nobo were showed better resistance reaction to enset bacterial wilt.…”
Section: Selections Of Disease Resistance Enset Clones Through Conventional Breeding Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, identification of resistant landraces has been challenging. Enset landraces with lower but varying susceptibility to Xvm infection (Ashagari, 1985;Archido & Tezera, 1993;Handoro & Michael, 2007;Welde-Michael et al, 2008;Tessera et al, 2008;Haile et al, 2014Haile et al, , 2020Hunduma et al, 2015;Wolde et al, 2016;Handoro & Said, 2016) have been reported. However, inconsistency in response to Xvm has been observed (Ashagari, 1985;Handoro & Michael, 2007;Welde-Michael et al, 2008;Tessera et al, 2008), potentially due to variation among batches of Xvm inoculum and its storage.…”
Section: Introductionmentioning
confidence: 99%